2017
DOI: 10.3390/ijerph14121532
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Gestational Diabetes Mellitus: A Cross-Sectional Study in China

Abstract: Objectives: This study aimed to identify the prevalence of gestational diabetes mellitus (GDM) and to examine its associations with social and behavioral factors, maternal body mass index (BMI), anemia, and hypertension. Methods: A cross-sectional analysis was performed on data collected from 2345 pregnant women from 16 hospitals in five selected provinces in mainland China. Results: Prevalence of GDM was as follows: overall: 3.7%; pregnant women in the first pregnancy: 3.4%; pregnant women in the second pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 46 publications
2
40
0
3
Order By: Relevance
“…The risk factors for GDM include age, family history of diabetes, obesity, history of neonatal death, race, ethnicity, history of abortion, history of preeclampsia, and history of previous gestational diabetes . The prevalence of GDM is correlated with the number of pregnancies, and women in their first and second pregnancies showed prevalence rates of 3.4% and 4.6%, respectively . The results of these studies showed that the prevalence of GDM increases with maternal age .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The risk factors for GDM include age, family history of diabetes, obesity, history of neonatal death, race, ethnicity, history of abortion, history of preeclampsia, and history of previous gestational diabetes . The prevalence of GDM is correlated with the number of pregnancies, and women in their first and second pregnancies showed prevalence rates of 3.4% and 4.6%, respectively . The results of these studies showed that the prevalence of GDM increases with maternal age .…”
Section: Discussionmentioning
confidence: 97%
“…One study reported both the crude and adjusted RRs, and three other studies reported both the crude and adjusted ORs of the effect of the prepregnancy BMI (as a categorical variable) on the risk of GDM. In these studies, the RR and OR were adjusted for maternal age, race/ethnicity, history of spontaneous abortion, education, family history of diabetes, place of residence, parity, smoking status, income, trimester of pregnancy, prepregnancy BMI, history of oligomenorrhea, and hypertension . After the adjustment of these GDM risk factors, the risk of GDM was found to be directly and significantly related to BMI, as similar to the results of the present meta‐analysis and the three other studies, which reported BMA as a continuous variable.…”
Section: Discussionmentioning
confidence: 99%
“…Some metaanalyses have shown that the risk of GDM is directly related to prepregnancy BMI and pregnancy weight gain [27][28][29][30]. One study reported both the crude and adjusted ORs and RRs [30], and three other studies reported the crude and adjusted ORs or RRs of the effect of prepregnancy BMI (as a categorical variable) on the risk of GDM [36][37][38], which were adjusted for potential confounders, such as maternal age, ethnicity, family history of diabetes, education level, parity, and smoking status. After the adjustment of these GDM risk factors, these previous findings were consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in Italy 36 , the Netherlands 37 , and Australia 38 suggested that lower SES was associated with GDM, while a study in India 39 found higher SES was associated with GDM. In China, a study in Wuhan 40 suggested higher educational lever was inversely associated with risk of GDM, while other studies in Beijing 17 and Chongqing 41 indicated no association between SES and GDM diagnosis. Consistent with these results in Beijing and Chongqing, our study also suggests no association between socioeconomic factors and GDM.…”
Section: Discussionmentioning
confidence: 96%